LOCAL FASHION PURCHASE INTENTION: THE ROLE OF ATTRACTIVENESS, TRUSTWORTHINESS AND EXPERTISE OF INFLUENCERS - Adelia Angelina Benya Cham; Miharni Tjokrosaputro (Graduate Program of Universitas Tarumanagara, 2024)
Product marketing activities through social media influencers are a marketing program that is being widely used, based on statistical data released by Statista in September 2023, showing that the market share of Influencer Marketing globally has increased quite rapidly from 2016-2023. This research aimed to test the influence of attractiveness, trustworthiness, and expertise as the credibility of social media influencers and its impact on the purchase intention of local fashion brand. The sample for this research was collected through a questionnaire distributed on online applications such as Instagram, Line, and Whatsapp, using both purposive sampling and non-probability sampling techniques. The collected sample comprised 238 valid respondents who met the criteria of being local fashion brand consumers and following or having at least seen influencer marketing local fashion brand products on social media, including Bella Clarissa @bellacrls_, Sashfir @sashfir_, Shavira Wangsamulia @shav_ira, Melle @mellexmicheline, Laura Siburian @laurasiburian, and Kezia Aletheia @keziaaletheia. The data obtained were then processed using the Structural Equation Model (SEM) method via the SMART-PLS 4.0 application. The research result indicates that trustworthiness and expertise have positive and significant influence on purchase intention of local fashion brand. In contrast, attractiveness has a positive and insignificant effect on local fashion brand purchase intention.